Steel Straps Confined Lightweight Foamed Concrete - Faisal Amsyar, Redzuan; Ma, Chau Khun; Abdullah Zawawi, Awang; Shek, Poi Ngian (Penerbit UTM Press, 2021)
Lightweight foamed concrete is originally unable to be used for main structural members such as column, beam and slab due to its low in compressive strength and ductility. Utilizing the external (active) confinement to confine the concrete laterally is one of best way to enhance the strength and ductility of the lightweight foamed concrete. However, lack of understanding in confined lightweight concrete will lead to an uneconomical design and overestimation in ultimate capacities. Hence, it is important to study in-depth on the structural behaviour of the confined lightweight foamed concrete and the effectiveness of external confinement using low-cost steel straps with an innovative pre-tensioning and multilayer techniques to the lightweight concrete columns. This book describes the general behaviour of steel straps confined lightweight foamed concrete and its performance onto the strength, deformability and ductility with some variant of parametric studies. Experimental approach is one of the useful methods to investigate the mechanical behaviour of unconfined and confined lightweight foamed concrete. In this study, a total of 36-cylinder specimens with 100 mm in diameter and 200 mm in height were tested under axial compression load and comparisons of laboratory data with the existing ultimate strength and stress-strain models is carried out in order to investigate in-depth on the behaviour of confined lightweight foamed concrete with pre-tensioned steel straps. This book may attract major attentions of researchers, designers and manufacturers that using lightweight concrete as part of the structural members in construction. Recent study shows a significant increment trend of implementing lightweight concrete in construction industry. Therefore, it is important to provide some basic information related to the confined lightweight concrete especially to the ultimate strength, ductility and stress-strain curvatures. Early investigation found out that the strength of confined lightweight foamed concrete columns is significantly improved by a rate related to the number of layers and spacing of steel straps confinement. Last but not least, the authors wish to express their appreciations to Universiti Teknologi Malaysia and the respective research team. A warm gratitude is also extended to the staff of Faculty of Engineering and Laboratory of Structure and Materials for their endless supports.